Entre textos e imagens: representações femininas em livros didáticos de história (2008 – 2014) - Martins, Cristiane da Silva Lima (2018)
This dissertation aims to analyze the representation of women in history textbooks directed to the last years of Elementary School (8th and 9th grades), used in the public schools of Brazil, approved by the Programa Nacional do Livro Didático (PNDL) [The National Program of Textbook] in 2008, 2011, and 2014. Among the questions contained in the dissertation, there is the concern about the way in which the performance of women as historical agents was built up over the years in didactic materials. The analysis focuses on the texts and images included in the following textbooks: História, Sociedade & Cidadania (2006), Projeto Araribá (2007), and Estudar História: Das origens do homem à era digital (2011), since textbooks are important tools in the process of consolidation and propagation of representations. Hence, we sought to think the sphere of women’s representation in the textbooks created after a period of educational reforms: the process of evaluation of the textbooks undertaken by PNDL, which has started in the beginning of 1996; the elaboration of the Parâmetros Curriculares Nacionais (PCNs) [National Curriculum Parameters], in 1998; and the Diretrizes Curriculares Nacionais (DCNs) [National Curriculum Guidelines], in 2013. Furthermore, we have tried to problematize what will be, from now on, the possibilities of change, also in history textbooks, after the approval of the Base Nacional Curricular Comum (BNCC) [National Curricular Common Base] in 2017. The analysis of the sources allowed us to verify that most of the contents, in the textbooks, continue to privilege the political and economic aspects. In this way, the approaches on women, when mentioned, appear in complementary texts, separated from the main subject. The study of representations, as proposed by Roger Chartier, was the basis for the construction of the analyzes that constitute this work.